O błędach i racjach w kontrolingu - Bieńkowska, Agnieszka; Kral, Zygmunt; Zabłocka-Kluczka, Anna (About mistakes and points in controlling, 2005)
Comprehension and concept of controlling were considered. Differences between controlling components and functions were characterized. Their interpretation was also presented. Process orientation of controlling was pointed out.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 208-216